1993
DOI: 10.1111/j.1475-4754.1993.tb01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Distribution of Lipid in Archaeological Ceramics: Implications for Sampling Potsherds for Organic Residue Analysis and the Classification of Vessel Use

Abstract: Organic residue analysis has heen performed on 62 reconstructed vessels from a single archaeological site ( Raunds, Northamptonshire. U . K . ) . In order to establish regions of lipid accumulation within a vessel, sherds were sampled from different purrs .f' u vessel, ,for e.xample base. body and rim, andsubmitred lo lipidc,.rtractionprocedure.s. The techniques c, f high-temperature gas chromatography (GC) and CClmass spectr0metr.y (GCIMS) were then used to analyse the sherd lipid extracts. The quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
9

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(154 citation statements)
references
References 7 publications
(5 reference statements)
5
140
0
9
Order By: Relevance
“…Esse resultado pode ser interpretado como sendo devido à maior variabilidade de uso a que estão sujeito os vasilhames de cerâmica. Por ex., os vasilhames utilizados para cozinhar apresentam concentrações de lipídios maiores que aqueles usados para estocagem 31 . A presença de lipídios provenientes da combustão não foi detectada nos fragmentos analisados.…”
Section: Resultsunclassified
“…Esse resultado pode ser interpretado como sendo devido à maior variabilidade de uso a que estão sujeito os vasilhames de cerâmica. Por ex., os vasilhames utilizados para cozinhar apresentam concentrações de lipídios maiores que aqueles usados para estocagem 31 . A presença de lipídios provenientes da combustão não foi detectada nos fragmentos analisados.…”
Section: Resultsunclassified
“…It is not known which part of the vessel the sherds originate from but it may be these come from points near the base, middle and rim of the vessel (cf Charters et al 1993). These plotted firmly within the ruminant adipose section (Fig.…”
Section: Near Latakwenymentioning
confidence: 99%
“…It has been shown that these lipid residues directly re£ect the original contents of ceramic vessels . A whole range of commodities, including olive oil, animal fats, beeswax and leaf waxes, have been identi¢ed by such analyses (Condamin et al 1976;Evershed et al 1991;Charters et al 1995Charters et al , 1997Evershed et al 1997a,b). Analysis of solvent-extractable lipids absorbed within the pottery matrix has also revealed information on the usage of ceramic vessels, by using quantitative analysis of the lipid pro¢le down a pot to di¡erentiate between cooking (with and without water) and storage vessels (Charters et al 1993(Charters et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Degraded animal fats are the most common types of organic residue detected in domestic pottery vessels, particularly in cooking jars and certain specialist types of bowls (Rottla« nder 1990;Charters et al 1993). The extracts typically comprise a mixture of triacylglycerols, diacylglycerols, monoacylglycerols and free fatty acids.…”
Section: Introductionmentioning
confidence: 99%